2009
DOI: 10.1080/18128600903200596
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of discrete choice and neural network approaches for modelling driver compliance with traffic information

Abstract: This article evaluates dynamic driver behaviour models that can be used, in the context of intelligent transport systems (ITS), to predict drivers' compliance with traffic information. The inputs to this type of models comprise drivers' individual socio-economic characteristics and other variables that may influence their compliance behaviour. The output is a binary integer representing whether drivers comply with travel advice or not. Two approaches are available for formulating this category of classificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…These models based on utility theory assume a utility function with observed variables and a random component capturing the unobserved factors that affect the individual's choice, and the random component may follow some assumed distributions. Dia and Panwai (2010) argued that assumptions of perfect information and decision-making capability of individuals in the discrete choice model may not be satisfied in some problems, and the complex relationship of imperfect input should be better modelled with other approaches. Their paper proposed an artificial neural network (ANN) model, and showed that ANN is superior to, in terms of classification rate, the discrete-choice models for the prediction problem of driver compliance with traffic information.…”
Section: Overview Of Related Workmentioning
confidence: 98%
“…These models based on utility theory assume a utility function with observed variables and a random component capturing the unobserved factors that affect the individual's choice, and the random component may follow some assumed distributions. Dia and Panwai (2010) argued that assumptions of perfect information and decision-making capability of individuals in the discrete choice model may not be satisfied in some problems, and the complex relationship of imperfect input should be better modelled with other approaches. Their paper proposed an artificial neural network (ANN) model, and showed that ANN is superior to, in terms of classification rate, the discrete-choice models for the prediction problem of driver compliance with traffic information.…”
Section: Overview Of Related Workmentioning
confidence: 98%
“…A number of studies have employed NN models largely to model the diversion under the influence of en route traffic information. The history of such studies goes back to as early as 1990 [20][21][22]. A few studies also evaluated the quality of the traffic information by using NN models [23].…”
Section: Multinomial Logit Modelmentioning
confidence: 99%
“…A few studies also evaluated the quality of the traffic information by using NN models [23]. In a more recent and relevant study, Dia and Panwai [22] analyzed the drivers' diversion given en route traffic information using both discrete choice models as well as an NN model. In this study, no attempt was made to identify the contributing factors (explanatory variables) to the diversion behavior for the undertaken case study in Australia.…”
Section: Multinomial Logit Modelmentioning
confidence: 99%
“…When compared to different ML algorithms that model travel mode choice, ANNs, DTs, SVMs and CA algorithms [89] FA F Other Xian-Yu (2011) [98] FA SVM BP Dia and Panwai (2010) [104] FA F BP Zhang and Xie (2008) [88] FA SVM BP Dia and Panwai (2007) [105] CLA Hybrid Other Andrade et al (2006) [87] FA F Other Celikoglu (2006) [39] CLA RBF LM Xie et al (2003) [86] CLA MLP BP Cantarella and de Luca (2003) [38] CLA MLP BP Vythoulkas and Koutsopoulos (2003) [84] FA F BP Mohammadian and Miller (2002) [83] CLA MLP BP Nijkamp et al (1996) [106] FA MLP BP Shmueli et al (1996) [81] CLA MLP BP 1 : CLA: Classification, FA: Function Approximation. 2 : RF: Random Forests, SVM: Support Vector Machines, F: Fuzzy, RBF: Radial Basis Function, MLP: Multi-Layer Perceptron.…”
Section: Discussionmentioning
confidence: 99%